A study to determine the prevalence of oxidised low-density lipoprotein in retinal venous occlusion in a population of West Bengal - Kapil Deb Lahiri; Gupta, Amit Kumar; Biswas, Utpal Kumar (Asian Journal of Medical Sciences, 2023)
Background: Oxidized low-density lipoprotein (ox-LDL) has been implicated in both coronary artery disease and retinal vein occlusion (RVO) because of atherosclerosis. However, there is no study to show the prevalence of ox-LDL in RVO till date. Aims and Objectives: This study aimed to find the prevalence of ox-LDL in RVO in a population of West Bengal. Materials and Methods: A 2-year prospective cross-sectional study of consecutive, unrelated adult patients, with a diagnosis of RVO, attending the outpatient department in a Medical College, was taken up for study. A pilot study was done to determine the expected prevalence of ox-LDL. Sample size was calculated based on the formula n=d2z2pq(z=1.96, d=0.04, p=0.196, q=0.804, n=minimum sample size). ox-LDL was measured in a total of 512 subjects who were selected based on the inclusion and exclusion criteria. Results: In this study, 272 males (aged 50 ± 7.2 years) and 240 females (aged 46 ± 7.7 years) with RVO were screened for ox-LDL. Elevated ox-LDL levels were found in 142 patients out of 512 participants in this study (27.7%). Moreover, 102 cases (19.9%) were found to have both raised LDL and ox-LDL, whereas 40 RVO cases (7.8%) had only elevated ox-LDL among the study participants. 71.8% of 142 RVO cases with elevated ox-LDL levels also had raised LDL levels, whereas remaining 28.2% had normal LDL cholesterol levels. Conclusion: It is high time to look beyond the traditional lipid parameters such as ox-LDL cholesterol levels as a risk factor of RVO. This study proved that ox-LDL cholesterol is highly prevalent in RVO cases. Thereby, proper screening of ox-LDL is a must as a tool for risk reduction of RVO cases, especially in a population with normal LDL cholesterol levels.